PAPERLESS HEALTHCARE: AS A TOOL TO BOOST AMERICAN HEALTHCARE AND ASSOCIATED CHALLENGES - Islamov, B.A; Teshayev , R.K (Innovative Development in Educational Activities, 2023)
The increased use of information technology (IT) in healthcare settings, particularly through the use of electronic health records (EHRs), which enable information to be easily shared and communicated among healthcare providers, has been advocated as a way to enhance care quality and support long-term cost control. However, rushing the installation of healthcare, IT would result in significant short-term financial outlays as well as a number of other issues that need to be resolved. Nevertheless, as a result of tracking patients, managing identities, creating medical records, and processing insurance claims, the healthcare industry will become a data-intensive industry. Therefore, security is important to maintain the confidentiality and integrity of such data in addition to other quality standards. Attention has been paid to IT technology as a way to support safe transactions and records, notably in the healthcare industry. In doing so, the extraordinary role of this technology in increasing reliability, and ensuring data security has been highlighted.